Acute kidney injury : basic research and clinical practice - Ding, Xiaoqiang; Rosner, Mitchell H.; Ronco, Claudio 1951- (Basel : Karger, 2018)
Acute Kidney Injury (AKI) is a complex syndrome that is prevalent among hospitalized patients. In recent years, occurrence of AKI events has risen due to a growing susceptibility of fragile and elderly subjects and an increase in the use of complex procedures such as cardiovascular surgery and imaging techniques. Exposure to potentially nephrotoxic drugs, such as new chemotherapeutic agents, is also proving to be a cause of AKI. This book summarizes recent advances in various settings. A reappraisal of current definitions and staging classifications for AKI in the literature is followed by a description of new criteria for identifying patients at risk and characterizing early kidney damage by using biomarkers. Other important topics include the sequelae of AKI and AKI in special populations such as children, the elderly, and those with cancer. The effects of AKI and its consequences on healthcare expenditures are also addressed from several perspectives. AKI management requires the cooperation of different specialists to optimize outcomes. This book is thus a perfect tool not only for nephrologists, but for every specialist involved in the complicated endeavor of improving patient care.
Keywords: INSUFICIENCIA RENAL AGUDA